The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1756284818786111
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effects of posterior tibial nerve stimulation on anorectal physiology in patients with faecal incontinence: a single centre experience

Abstract: Background:Posterior tibial nerve stimulation (PTNS) is a novel treatment for patients with faecal incontinence (FI) and may be effective in selected patients; however, its mechanism of action is unknown. We sought to determine the effects of PTNS on anorectal physiological parameters.Methods:Fifty patients with FI underwent 30 min of PTNS treatment, weekly for 12 weeks. High-resolution anorectal manometry, bowel diaries and Vaizey questionnaires were performed before and after treatment. Successful treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…This, however, is in contrast to some previous reports in both BF and PTNS. 18 As the variables most likely to improve following BF, for example anal squeeze pressure, 19 and following PTNS, for example anal resting pressure and rectal sensory volumes, 18 were numerically improved in our study but did not reach statistical significance the likely explanation for this finding is the small patient numbers. As physiological changes were defined as a secondary endpoint in the current study, power to detect change was limited, and it is possible that including more patients would replicate previous reports of some physiological improvements.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This, however, is in contrast to some previous reports in both BF and PTNS. 18 As the variables most likely to improve following BF, for example anal squeeze pressure, 19 and following PTNS, for example anal resting pressure and rectal sensory volumes, 18 were numerically improved in our study but did not reach statistical significance the likely explanation for this finding is the small patient numbers. As physiological changes were defined as a secondary endpoint in the current study, power to detect change was limited, and it is possible that including more patients would replicate previous reports of some physiological improvements.…”
Section: Discussioncontrasting
confidence: 65%
“…This is similar to previous reports of the time line of improvement in PTNS. 18 Nevertheless, data regarding efficacy in this trial should be interpreted with caution, as this was a small cohort, with no sham treatment arm, in a selected group of patients. This probably explains the unusually high rates of success at the end of treatment (92%), even as assessed by the objective measure of 50% or more improvement in FI episodes.…”
Section: Discussionmentioning
confidence: 95%
“…TNS, on the other hand, seems to have beneficial effects on the PR of patients with IF. In the study by Heywood et al, patients undergoing TNS showed a 6.8% increase in RP values, however without statistical significance, probably because of the small sample size and the short follow-up interval (13) .…”
Section: Discussionmentioning
confidence: 88%
“…A surface electrode is placed on the ipsilateral foot, medial to the calcaneum. Correct placement is confirmed by demonstrating either a motor response (plantar flexion of the great toe) or a sensory response (tingling to the toes, arch or heel) through incremental stimulation increases[ 9 , 13 ].…”
Section: Methodsmentioning
confidence: 99%